An Evaluation of Polycaprolactone Matrices for Vaginal Delivery of the Antiviral, Tenofovir, in Preventing Heterosexual Transmission of HIV. Issue 10 (31st July 2013) - Dang, Nhung T. T.; Sivakumaran, Haran; Harrich, David; Coombes, Allan G. A.
<x xml:space="preserve">Abstract</x> Tenofovir was incorporated in controlled‐release polycaprolactone (PCL) matrices designed for production of vaginal inserts for prevention of HIV transmission. Rapid cooling of suspensions of the drug powder in PCL solution resulted in micro‐porous matrices with tenofovir loadings up to 12% (w/w) and high incorporation efficiencies in excess of 90%. The release behaviour of tenofovir in simulated vaginal fluid (SVF) demonstrated high delivery efficiency of 85%–99% over 30 days and could be described effectively by a first‐order kinetics model giving a mean value of 0.126 day‐1 for the release constant (k1). Tenofovir released from PCL matrices into SVF exhibited high relative activity ranging from 70 to 90%, against pseudo‐typed HIV‐1‐infected HeLa cells. The inhibitory activity of tenofovir standard solutions in SVF provided an IC50 value of 2.38 μM. Besides confirming high levels of in vitro antiviral activity, the predicted concentrations of tenofovir, which would be released from a PCL intra‐vaginal ring in vivo, exceeded the IC50 value for HIV‐1 by a factor of 35–200 and clinically protective concentrations by a factor of 50. These findings recommend further investigations of antiviral‐loaded PCL matrices for controlling heterosexual transmission of HIV. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3725–3735, 2013